In situ X-ray diffraction study of a TiO2 nanopowder Spark Plasma Sintering under very high pressure. Issue 7 (July 2023) - Cottrino, Sandrine; Gaudisson, Thomas; Pailhès, Stéphane; Ferrara, Emanuela Archina; Mishra, Shashank; Daniele, Stéphane; Mézouar, Mohamed; Largeteau, Alain; Le Godec, Yann; Le Floch, Sylvie
Abstract: We investigated the effect of very high pressure on the sintering temperature, phase transition and the grain growth during Spark Plasma Sintering (SPS) of a 15 nm TiO2 nanopowder. Using in situ synchrotron X-ray diffraction during sintering at 1.5 and 3.5 GPa, we followed the evolution of the crystalline phases and the crystallite size as a function of temperature. In comparison, in the laboratory, SPS experiments were performed on two original facilities: A Paris-Edinburgh press and a high-pressure module adapted to standard SPS equipment. We studied the effect of the pressure on the sintering in the range 76 MPa to 3.5 GPa. We have shown that highly dense nanostructured ceramics can be prepared under very high pressure at low sintering temperatures. At 1 GPa, we limited the grain growth to an average size of 233 nm by heating at only 560 °C, and achieved a relative density of 98 %.